Effect of glazing application side and mechanical cycling on the biaxial flexural strength and Weibull characteristics of a Y-TZP ceramic - Carolina Machado Martinelli LOBO; Sâmia Carolina Mota Cavalcanti SACORAGUE; Nathalia Ramos da SILVA; Anna Karina Figueiredo COSTA; Larissa Marcia Martins ALVES; Marco Antônio BOTTINO; Mutlu ÖZCAN; Rodrigo Othávio de Assunção e SOUZA; Renata Marques de MELO (University of São Paulo, 2020)
Abstract Glaze application on monolithic zirconia (Y-TZP) can be a practical approach to improve the mechanical properties of this material. Objective Our study evaluated the effect of glazing side and mechanical cycling on the biaxial flexure strength (BFS) of a Y-TZP. Methodology Eighty sintered Y-TZP discs (Ø:12 mm; thickness: 1.2 mm - ISO 6872) were produced and randomly assigned into eight groups (n=10), according to the factors "glazing side" (control - no glazing; GT - glaze on tensile side; GC - glaze on compression side; GTC - glaze on both sides) and "mechanical aging" (non-aged and aged, A - mechanical cycling: 1.2×106, 84 N, 3 Hz, under water at 37°C). Specimens were subjected to BFS test (1 mm/min; 1,000 Kgf load cell) and fractured surfaces were analyzed by stereomicroscopy and SEM. Hsueh's rigorous solutions were used to estimate the stress at failure of glazed specimens. Two-way ANOVA, Tukey's test (5%), and Weibull analysis were performed. Results The "glazing side", "mechanical aging" and the interaction of the factors were significant (p<0.05). Groups GC (1157.9±146.9 MPa), GT (1156.1±195.3 MPa), GTC (986.0±187.4 MPa) and GTC-A (1131.9±128.9 MPa) presented higher BFS than control groups (Tukey, 5%). Hsueh's rigorous solutions showed that the maximum tensile stress was presented in the bottom of zirconia layer, at the zirconia/glaze interface. Weibull characteristic strength (σo) of the GC was higher than all groups (p<0.05), except to GT, GTC-A and GTC, which were similar among them. The fractography showed initiation of failures from zirconia the tensile side regardless of the side of glaze application and fatigue. Conclusion Glazing zirconia applied on both tensile and compression sides improves the flexural strength of Y-TZP, regardless the mechanical aging.